Structural equation models of management and decision‐making styles with job satisfaction of academic staff in Malaysian research university - Amzat, Ismail Hussein; Idris, Abdul Rahman (Emerald Group Publishing Limited, 2012)
Purpose – The purpose of this paper is to discuss the effect of management and decision‐making styles on the job satisfaction of academic staff in a Malaysian Research University.